2022
DOI: 10.1109/access.2022.3153051
|View full text |Cite
|
Sign up to set email alerts
|

Smart Optical Sensors for Internet of Things: Integration of Temperature Monitoring and Customized Security Physical Unclonable Functions

Abstract: Date of publication xxxx 00, 0000, date of current version xxxx 00, 0000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…Dias et al have indicated that creating a tailored security system for IoT devices is complex due to the IoT environment's diverse, divided, and non-interoperable nature [7]. Various security measures have been suggested to enhance information safety, authorization, access management, confidence, and privacy in connected devices.…”
Section: Background and Analysismentioning
confidence: 99%
“…Dias et al have indicated that creating a tailored security system for IoT devices is complex due to the IoT environment's diverse, divided, and non-interoperable nature [7]. Various security measures have been suggested to enhance information safety, authorization, access management, confidence, and privacy in connected devices.…”
Section: Background and Analysismentioning
confidence: 99%
“…Salah satunya dengan memanfaatkan kontak langsung dengan benda atau objek yang ingin diukur suhunya, tanpa kontak langsung dengan objek, dengan memanfaatkan perwakilan suhu dengan benda yang lain di lingkungan yang sama, dan lain lain [3]. Salah satu metode pengukuran yang umum dilakukan terutama pasca pandemi COVID -19 adalah pengukuran tanpa kontak langsung [4] [5]. Berbagai macam alat pengukuran suhu telah banyak pula digunakan untuk pengukuran tanpa kontak langsung [6][7] [8].…”
Section: Pendahuluanunclassified
“…At the same time, a structure with intrinsic sensing ability also has potential development prospects in the medical scenes . This methodology provides feasible and convenient solutions for the univocal identification and optical temperature monitoring using mobile phones and thus can be connected to the IoT directly …”
Section: Body Temperature and Thermal Comfortmentioning
confidence: 99%
“…199 This methodology provides feasible and convenient solutions for the univocal identification and optical temperature monitoring using mobile phones and thus can be connected to the IoT directly. 200…”
Section: Optical Systems For Personal Thermal Comfort Assessmentmentioning
confidence: 99%